Nutrient intake, productive performance and body measurements of dairy heifers fed with different sources of protein - Mota, Diego Azevedo; Berchielli, Telma Teresinha [UNESP]; Canesin, Roberta Carrilho [UNESP]; Rosa, Bruna Laurindo [UNESP]; Ribeiro, Andressa Ferreira [UNESP]; Brandt, Heitor Violin [UNESP] (Editora da Universidade Estadual de Maringá (EDUEM), 2013)
This study evaluated the effect of different protein sources (soybean meal, cottonseed meal, peanut meal and sunflower meal) on dry matter and nutrient intake, productive performance and body measurements of dairy heifers, Holstein x Zebu, recreated in confinement. The experiment consisted in a randomized complete block design made up by 6 replications and 4 treatments. The mean values of ingestion of ether extract (EEI, kg day-1) were statistically different (p < 0.05). The neutral detergent fiber intake (NDFI, %BW) also presented differences (p < 0.05), with higher values in the diet containing sunflower meal (1.01% BW) in relation to the diet with soybean meal (0.84% BW). The average daily weight gain using the diet with soybean meal was superior (0.95 kg day-1) to the diet with sunflower meal (0.82 kg day-1), and considering the final body weight, the diet with soybean meal was superior to the other treatments (p < 0.05). The heart girth presented greater association with body weight (0.93). The soybean meal promoted the best productive performance of crossbred Holstein x Zebu heifers fed diets based on sugarcane. However, cottonseed meal, peanut meal and sunflower meal can be possible alternatives to soybean meal.

Objetivou-se avaliar o efeito de diferentes fontes proteicas (farelo de soja, farelo de algodão, farelo de amendoim e farelo de girassol) sobre o consumo de matéria seca e nutrientes, desempenho produtivo e medidas corporais de novilhas leiteiras, mestiças Holandês x Zebu, recriadas em confinamento. O delineamento experimental foi em blocos completos casualizados, constituído por seis repetições e quatro tratamentos. Os valores médios de ingestão de extrato etéreo (IEE, kg dia-1) apresentaram diferença estatística (p < 0,05). A ingestão de fibra em detergente neutro em % do peso corporal foi superior (p < 0,05) na dieta com farelo de girassol (1,01 %PC) em relação à dieta com farelo de soja (0,84 %PC). O ganho médio de peso corporal promovido pela dieta com o farelo de soja foi superior (0,95 kg dia-1) à dieta com farelo de girassol (0,82 kg dia-1), e no peso corporal final a dieta com o farelo de soja foi superior aos demais (p < 0,05). A medida biométrica perímetro torácico apresentou maior grau de associação com o peso corporal (0,93). O farelo de soja proporciona melhor desempenho produtivo a novilhas mestiças Holandesa x Zebu, alimentadas com dietas à base de cana-de-açúcar. Contudo, o farelo de algodão, farelo de amendoim e farelo de girassol pode ser possíveis substitutos do farelo de soja.
Consumo de nutrientes, desempenho produtivo e medidas corporais de novilhas leiteiras alimentadas com diferentes fontes proteicas
Keywords: body measurement; daily gain; protein concentrate; Sugarcane; medidas corporais; ganho diário; concentrados proteicos; Cana-de-açúcar